Exponential stability of a PI plus reset integrator controller by a sampled-data system approach. (August 2018) - Davó, M.A.; Gouaisbaut, F.; Baños, A.; Tarbouriech, S.; Seuret, A.
Abstract: The paper deals with the stability analysis of time delay reset control systems, for which the resetting law is assumed to satisfy a time-dependent condition. A stability analysis of the closed-loop system is performed based on an appropriate sampled-data system. New linear matrix inequality (LMI) conditions are proposed to ensure the exponential stability of the closed-loop system resulting from the connection of a plant with a proportional and integral controller together with a reset integrator (PI+RI). Highlights: A time-delay reset control system based on a PI plus reset integrator controller. Formulation of the reset control system into the framework of sampled-data systems. Exponential stability criteria in the form of LMIs based on the Lyapunov–Krasovskii method and a looped-functional. Exponential stabilization of unstable base systems by forcing reset actions.